Study of the association of the known prognostic variables with EGFR expression in head and neck squamous cell carcinomas - Toyaja Jadhav; Ajay Malik; Ahmed Waheed Kashif; Divya Shelly; Prabhashankar S Mishra; Ajay Kumar Baranwal; Rajesh Sahu (Wolters Kluwer Medknow Publications, 2024)
Context: Head and neck squamous cell carcinomas (HNSCCs) are the sixth most frequent malignancy in the world. Epidermal growth factor receptors (EGFRs) are members of Erb B family of receptors. EGFR is known to act as a driver of tumorigenesis in various carcinomas. Over expression of EGFR in HNSCC is associated with poor prognosis and resistance to radiotherapy. It is a useful prognostic marker, marker for response to therapy, and also a therapeutic target. Aim: To study the association of the known prognostic variables with EGFR expression in HNSCCs and to correlate it with the clinical outcome Settings and Design: Cross-sectional observational study. Materials and Methods: A total of 170 patients of HNSCC were evaluated for EGFR expression and followed up for at least two years, with correlation of EGFR expression with various histopathological factors and their clinical outcome. Statistical Analysis Used: Chi-square test. Results: The expression of EGFR in HNSCC in this study population was 88.82%. Statistical significance was noted between EGFR reactivity and age of the patient, its histological grade and perineural invasion. Statistical significance was also noted between EGFR reactivity and recurrence of malignancy as well as the site of recurrence. Conclusion: EGFR expression in patients with HNSCC is a poor prognostic biomarker and has a comparatively lower survival outcome as compared to non-EGFR expressing HNSCC cases. Hence, it will be helpful for all those patients diagnosed with HNSCC to ideally undergo an additional EGFR immunohistochemical evaluation, which, in turn, will help the oncologists in management of the tumor with anti-EGFR therapy combined with radiotherapy, to obtain a better response and a survival outcome.